Digital Transformation of Santri: Integrating Learning Organisation with Adaptive Learning in Pesantren - Manaf, Sofwan; Mona Novita; Miftah Hur Rahman Zh; Zahid Zufar At Thaariq; Athia Nur Kamilah (Edukasiana: Journal of Islamic Education, 2026)
Digital transformation in Islamic boarding schools requires integrating learning organization models with adaptive learning to address the challenges of the Industrial Revolution 4.0 and society 5.0. This article aims to analyze the construction of the integration of the two concepts in the context of digitization of students in Indonesian Islamic boarding schools. The study focuses on a technology-based adaptive learning model associated with the five Senge disciplines in pesantren governance. The method used is a Systematic Literature Review (SLR) following the PRISMA protocol, based on 35 Scopus- and Sinta-indexed articles published between 2015 and 2025. The results of the study show that the integration of learning organization and adaptive learning forms four dimensions of transformation, namely modernization of data-based curriculum, strengthening the digital capacity of ustadz and students, system-based governance, and preservation of Islamic values. These findings confirm that the Islamic boarding schools that have succeeded in transforming are those that make collective learning a culture and personalize learning as a strategy. It is concluded that the Senge-Adaptive Learning hybrid framework is feasible as a model for digital pesantren governance.